Land‐use changes interact with geology to facilitate dispersal of the rock hyrax (Procavia capensis) and leishmaniasis across Israel and the West Bank. Issue 3 (21st March 2023) - Ben‐Moshe, Noam; Rosensaft, Marcelo; Iwamura, Takuya
Abstract: Geology plays a fundamental role in establishing species' habitats, determining both physical (e.g., landscape morphology, soil texture) and chemical (e.g., mineral composition, water availability) properties. In the current Anthropocene epoch, human activity is transforming Earth's geology and ecosystems. Yet to date, there have been almost no studies incorporating geology when examining the effect of such land‐use changes on species distribution. This study seeks to uncover how specific land‐use changes interact with geology, in order to explain the recent and rapid expansion of the rock hyrax ( Procavia capensis ) across the mountains of central Israel and the West Bank. Hyraxes are dependent on rock mounds for their habitat, and their expansion seems to be correlated with increasing infrastructure construction. However, their expansion patterns differ among locations, even when the human land‐use is similar. To explain the patterns of hyrax distribution observed over the past 46 years, we converted geological data into ecological data, which present the probability of the local bedrock breaking into boulders, whether due to either natural or anthropogenic weathering processes. We applied species distribution models (SDMs) and found that the expansion of rock hyrax populations was facilitated by means of the interaction of specific geological units with land‐use practices (e.g., roads and construction), which resulted in the accumulation of large boulders, creating novel habitats and stepping stones in previously unsuitable areas for hyraxes. Since rock hyraxes are major hosts of the leishmaniasis pathogen, the findings from this study offer important insights into the progression and potential outbreaks of the disease in human populations. Understanding the role that geology plays in shaping a species' niche is expected to prove useful in studying the distribution of other wildlife species and is fundamental in studies seeking to predict the potential ecological impacts on local biodiversity associated with land‐use change. Abstract : Geology can play a significant role in dispersal ability of animals, especially when it interacts with land use, a subject that has received less study. We examined the causes of recent expansion of the rock hyrax, an important host of leishmaniasis, across Israel and the Palestinian Territories based on the distribution of geological units and human development. We demonstrate that rock hyrax expansion is facilitated where roads and construction intersect with specific rock formations, resulting in rock mounds that serve as new habitats for hyraxes.